2009
DOI: 10.1308/003588409x358971
|View full text |Cite
|
Sign up to set email alerts
|

Patients' Attitude Towards the Use of a Chaperone in Breast Examination

Abstract: INTRODUCTION The aim of this study was to assess the attitude and the preferences of patients towards the use of a chaper one during breast examination. PATIENTS AND METHODS A two-part questionnaire was circulated among 204 consecutive new patients, attending both symptomatic breast and screened assessment clinics. RESULTS A total of 200 questionnaires were fully completed and returned. Although 104 (52%) patients felt that they did not need a chaperone during breast examination, 65 (33%) preferred to have one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 4 publications
1
24
0
Order By: Relevance
“…This information will be important to female clinicians who have traditionally less frequently offered a chaperone during breast examinations. 6 8 11 12 This study, as others, 12 14 demonstrates that women are more likely to decline the offer of a chaperone when the examining clinician is female; 61.45% declined a chaperone offered by a female clinician compared to 3.82% declining if the clinician was male. The reverse of this is that nearly 40% of women will still choose a chaperone even with a female clinician.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…This information will be important to female clinicians who have traditionally less frequently offered a chaperone during breast examinations. 6 8 11 12 This study, as others, 12 14 demonstrates that women are more likely to decline the offer of a chaperone when the examining clinician is female; 61.45% declined a chaperone offered by a female clinician compared to 3.82% declining if the clinician was male. The reverse of this is that nearly 40% of women will still choose a chaperone even with a female clinician.…”
Section: Discussionsupporting
confidence: 50%
“… 9 10 Studies have also shown that many patients see the offer of a chaperone as a sign of respect from their doctor and helps build a good patient–doctor relationship. 5 6 …”
Section: Introductionmentioning
confidence: 99%
“…The majority of reports about patients' perceptions of a medical chaperone have focused on female patients [3][4][5][6][7] ; those of male patients are less well studied. [8][9][10] A potential discrepancy may exist between the two groups.…”
Section: 見證人與牽涉敏感部位的身體檢查: 男性和女性 病人的選擇mentioning
confidence: 99%
“…Inoue et al (2006) reported that female patients experience stress when undergoing intimate care provided by male nurses. Although the presence of a chaperone is viewed as a sign of respect and protection (Sinha et al 2009), Inoue et al (2006) revealed that female patients would much prefer a female nurse to provide care. However, on some occasions this may not be an option.…”
Section: Difficulties Facing Male Nurses Providing Intimate Carementioning
confidence: 99%